KEPEMIMPINAN KEPALA SEKOLAH (Studi Situs Sekolah Menengah Kejuruan Negeri 2 Karanganyar) - Sawitri , Retno (2010)
This study aims to (1) describe the spatial characteristics of the school at Vocational School Site Study II Karanganyar, (2) describe the characteristics of teachers working relationship with the principal at Vocational School Site Study II Karanganyar, (3) describe the characteristics of school principals as social participants in society.The research was done in Vocational School Site Study II Karanganyar perspective using qualitative approach. To obtain the data in the study used methods of interviews, observation, and documentation. Data analysis was carried out through three stages, namely: data reduction, data presentation and conclusion / verification. The results of this study were (1) School of Spatial Characteristics of Vocational School Site Study II Karanganyar. Room school in Vocational School Site Study II Karanganyar, consisting of several rooms with a number of educational needs, can be used and function as it should. School hall has been arranged in accordance with their respective functions, each room is equipped with the necessary furniture and equipment. The arrangement of space and the teachers' lounge arranged based on the principle facilitate cooperation and the principle of supervision with the aim to create a comfortable working atmosphere. (2) Characteristics of teachers working relationship with the principal at Vocational School Site Study II Karanganyar. Relations with the principal teacher at Vocational School Site Study II Karanganyar occurred at the time service, and relationships outside of work hours on duty, be open so that teachers can communicate any problems to the school principal at all times, both within hours of service, or outside the hours of service. The existence of the open nature of the principal is able to create good communication between teachers and principals and vice-versa. (3) Characteristics of Head of School For Social Participants in the Community. The headmaster always live in the community, so that principals in the community regarded as community leaders and public figures. The school principal has a good personality competence so that principals can be friendly, kind, courteous to all citizens by not distinguishing status, gender, race, or religion. Amid public school principal has an open attitude, do not distinguish each other, can get along with all citizens both young and old, among the people, like friends, and active in kemasyarkatan.